Perception of nursing care for dependents rehabilitation of psychoactive substances in the light of social learning - Victoria , Castillo Zamora Luz; Yolanda , Rodríguez Núñez; Mayela , Cajachagua Castro (International Journal of Psychosocial Rehabilitation, 2026)
The objectives were to analyze the perception of care provided by the nurse dependent on psychoactive in the light of social care learning and performing with cognitive behavioral model during the rehabilitation process substances people. It corresponds to the qualitative approach, descriptive-exploratory type. Study subjects were five nurses working in a Rehabilitation Center in Lima, Peru. Technique semistructured interviews and Hermenéutica technique for analysis was used. Two categories are unveiled: The conception of nursing care, which is based on support, concern, support and involvement, factors contributing to a change of lifestyle. The second category is the providing nursing care applying social skills within the framework of cognitive behavioral model. The perception of care that provide dependent on psychoactive substances person is basis for recognizing that its presence through its essence, way of being and personal experience ensure a permanent and individualized holistic care where self-help skills are applied and mutual aid rehabilitation based on social learning approach.